Experimental infection of mice with noncytopathic bovine viral diarrhea virus 2 increases the number of megakaryocytes in bone marrow - Kyung-Hyun Lee (Virology Journal, 2018)
Abstract Background Bovine viral diarrhea virus (BVDV) causes significant economic losses worldwide in the cattle industry through decrease in productive performance and immunosuppression of animals in herds. Recent studies conducted by our group showed that mice can be infected with BVDV-1 by the oral route. The purpose of this study was to assess the clinical signs, hematological changes, histopathological lesions in lymphoid tissues, and the distribution of the viral antigen after oral inoculation with a Korean noncytopathic (ncp) BVDV-2 field isolate in mice. Methods Mice were orally administered a low or high dose of BVDV-2; blood and tissue samples were collected on days 2, 5, and 9 postinfection (pi). We monitored clinical signs, hematological changes, histopathological lesions, and tissue distribution of a viral antigen by reverse transcription-polymerase chain reaction (RT-PCR) and immunohistochemistry (IHC) and then compared these parameters with those in ncp BVDV-1 infections. Results None of the infected mice developed any clinical signs of the illness. Significant thrombocytopenia was found in both low- and high-dose-inoculated mice on day 2 pi. Leukopenia was apparent only in low-dose-inoculated mice on day 2 pi, whereas lymphopenia was not observed in any ncp BVDV-2-infected animal. Viral RNA was found in the spleen in of low- and high-dose-inoculated mice by RT-PCR. According to the results of IHC, the viral antigen was consistently detected in lymphocytes of bone marrow and spleen and less frequently in bronchus-associated lymphoid tissue (BALT), mesenteric lymph nodes, and Peyer’s patches. Despite the antigen detection in BALT and mesenteric lymph nodes, histopathological lesions were not observed in these tissues. Lympholysis, infiltration by inflammatory cells, and increased numbers of megakaryocytes were seen in Peyer’s patches, spleens, and bone marrow, respectively. In contrast to ncp BVDV-1 infection, lympholysis was found in the spleen of ncp BVDV-2-infected mice. These histopathological lesions were more severe in high-dose-inoculated mice than in low-dose-inoculated mice. Conclusions Our results provide insight into the pathogenesis of ncp BVDV-2 infection in mice. Collectively, these results highlight significant differences in pathogenesis between ncp BVDV-1 and ncp BVDV-2 infections in a murine model.